"Is it all just lip service?": on Instagram and the normalisation of the cosmetic servicescape. Issue 1 (26th November 2021) - Rodner, Victoria; Goode, Amy; Burns, Zara
Abstract : Purpose: To better understand the uptake of cosmetic procedures in the wake of Instagram, this study aims to unravel how the aesthetic labour of influencers acts as the packaging of the cosmetic servicescape. In doing so, the authors contribute to theorising of aesthetic and emotional labour within the services marketing literature, fleshing out the bodywork of influential others not as employees but endorsers, who act like the "walking billboards" (Zeithaml and Bitner, 2003) for the cosmetic service industry. Design/methodology/approach: This study adopts a dual qualitative approach to data collection, coupling netnographic material from Instagram posts with 16 in-depth interviews with female Instagram users who have undergone or hope to undergo cosmetic surgery. Using mediated discourse analysis, the authors weave their visual and discursive data together for a richer account of the commoditisation of cosmetic surgery. Findings: Adopting a postfeminist neoliberal lens, where women are viewed as aesthetic entrepreneurs who are constantly working on the body and the self, the findings of the study reveal how influencers' aesthetic and emotional labour help package, propagate and demystify the cosmetic servicescape. Through their visual storytelling, we see how influencers help endorse (local) cosmetic services; commoditise cosmetic procedures through the conspicuous display of their ongoing body projects whilst masking the labour and pain involved; and how face-filters that use augmented reality (AR) technology foster new forms of (digitised) body dysmorphia. Originality/value: The authors shed light on the darker side of social media and body-enhancing technologies, where tales of body transformation trivialise cosmetic intervention and AR technology induces a digitised body dysmorphia.